War of the waves: Radio and resistance during World War II - Stefano Gagliarducci; Massimiliano G. Onorator; Francesco Sobbrio; Guido Enrico Tabellini (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2018)
What is the role of the media in coordinating and mobilizing insurgency against a foreign military occupation? We analyze this question in the context of the Nazi-fascist occupation of Italy during WWII. We study the effect of BBC radio counter-propaganda (Radio Londra) on the intensity of internal resistance to the Nazi-fascist regime. Using variation in monthly sunspot activities affecting the sky-wave propagation of BBC broadcasting towards Italy, we show that BBC radio had a strong impact on political violence. We provide further evidence to prove that BBC radio played an important role in coordinating resistance activities, but had no lasting role in motivating the population against the fascist regime.
Keywords: D74; L82; N44; 330; Media; BBC; Counter-propaganda; Insurgency; Violence; WWII; Sunspots